Analysis of Financial Ratio at PT. Indofood Sukses Makmur Tbk in 2020-2022 - Anjel Monika LT; Bon Jovi M Panjaitan; Emya M. K Tumangger; Rahma Nadila Ulfa (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to evaluate the financial performance of PT Indofood Sukses Makmur Tbk using relevant financial ratios for the 2020-2022 period. The methodology used includes descriptive analysis and quantitative analysis. Financial ratio analysis consists of liquidity ratios, profitability ratios, activity ratios, and solvency ratios. The results showed that in 2022, the liquidity ratio increased significantly while the solvency ratio decreased. The activity ratio has increased after experiencing a decline in 2021, and the profitability ratio has decreased every year. The average financial ratio yield in 2020 was better than the following two years. This research provides new insights into the importance of using financial ratios in evaluating a company's financial performance and can improve understanding of the importance of financial ratios in business decision making.